Study of the acoustic resonance occurring in a multistage high-speed axial compressor. (September 2013) - Courtiade, Nicolas; Ottavy, Xavier
A study of the acoustic resonance occurring and leading to surge in the 3½-stage high-speed compressor CREATE (rotation speed: 11543 r/min, rotor 1 tip speed: 313 m/s) is presented in this paper. It is based on high-frequency wall static pressure measurements performed all along the machine from peak efficiency to surge. In this paper, a model of acoustic resonance will be applied to the experimental results. The axial distribution of the amplitude of the acoustic modes is first analyzed. Then, a study of the reflections occurring in the machine will be done in order to understand the mechanisms responsible for the resonance.